Evaluation and Quantification of Electromagnetic Field Distribution for Different Configurations of Aeronautical Materials - Bennoud, Salim; Zergoug, Mourad (Review of Industrial Engineering Letters, 2017)
The electromagnetic field distributions are of great importance in various engineering applications, especially in aeronautical industry due to the presence of the communication systems, the embarked radars and antennas as well as the electric circuits and components on aircraft that requires to take account of the influence of these devices on their environment and in particular of their interactions with the material. This paper shows how electromagnetic field distributes across different aeronautical materials. This problem is solved using computational electromagnetic, such as the finite elements method, to resolve Maxwell’s equations through the problem geometry using an in-house code developed during this work. Obtained results enable to calculate the field values in any place of the studied geometry and determinate the related physical parameters. Results show that parameters such as material properties, used frequency and sample dimensions have a strong influence on the field distribution. This dependence could have important consequences to characterize and optimize conditions to choose materials used in electromagnetic applications. For particular cases these results are compared with open-source codes. The results are very similar with a good precision which enables to use the developed code to carry out simulations for other geometries of materials with different proprieties.